Deterring rodent seed‐predation using seed‐coating technologies. Issue 4 (14th April 2020) - Taylor, Justin B.; Cass, Kristina L.; Armond, David N.; Madsen, Matthew D.; Pearson, Dean E.; St. Clair, Samuel B.
Abstract : With many degraded environments undergoing restoration efforts, there is a growing need for the optimization of direct seeding practices. Seeds planted on wildlands are often consumed by rodents, leading to reduced plant establishment. Coating seeds in rodent aversive products may prevent seed‐predation. We tested 10 seed‐coating formulations containing products expected to deter rodents, namely: ghost and cayenne pepper powders; essential oils from bergamot, neem, and pine; methyl‐nonyl‐ketone, anthraquinone, activated carbon, beta‐cyclodextrin, and a blank coating containing no rodent deterrents to serve as a control treatment. Each treatment was applied to Pseudoroegneria spicata (bluebunch wheatgrass) seeds. These seeds germinated similarly to uncoated control seeds unless the coating contained methyl‐nonyl‐ketone which reduced germination. When seeds were offered to Ord's kangaroo rats ( Dipodomys ordii ), they strongly avoided the treatments in favor of uncoated control seeds. Notably, the blank coating, lacking active ingredients, still elicited 99% avoidance. However, these results indicated behavior when alternative food sources are readily available, a scenario rare in nature. To address this, a second feeding experiment was conducted to observe D. ordii 's behavior under calorie‐restricted conditions. D. ordii were subjected to a fast period, then offered only one treatment. Under these conditions, many subjects chose to consume coated seeds, but to a lesser degree than subjects offered control seeds. Seeds coated in ghost pepper, neem oil, and activated carbon reduced consumption by 47–50%. Given these lab results, we would expect these treatments to increase native plant establishment following the direct seeding of wildlands by protecting seeds from rodent predation.